KEPEMIMPINAN KIAI SALAF DI PONDOK PESANTREN AL-HASANI AL-LATIFI BONDOWOSO - Mustajab Mustajab (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2019)
As the oldest and typical Indonesian educational institution, pesantren has a significant role in educating the nation's children. the character of education and leadership is very influential on the students' character who is the younger generation. Besides that, pesantren in the archipelago are very diverse when viewed from the aspect of the material character being taught, the teaching methods, the students' quantity, the leadership model of their leaders, the characteristics of their movements, and their affiliation to Islamic movements in the archipelago. Pesantren salaf which has survived until now seen as special pesantren, because such pesantren considered as institutions that are able to maintain their existence in the midst of information which is a catalyst for change in society. Therefore, leadership in the Pesantren salaf is very interesting to be observed. This dissertation tries to discuss the types and styles of leadership of pesantren in the modern world at two salaf pesantren located in Bondowoso. Namely, Pesantren Kauman al-Hasani al-Lathifi. The result is leadership in the Salaf Al-Hasani al-Latifi is leadership based on lineage and wise autocratic character. Its style is a delegative leadership style.